Anal Fistula of Crypto-Glandular Etiology: A Review of the Literature with a Step-by-Step Approach for Diagnosis and Surgical Management - Charalampopoulos, Anestis; Bagias, George; Bompetsi, Georgia; Nastos, Kostantinos; Papagrigoriadis, Savvas; Papaconstantinou, Dimitrios (International Journal of Innovative Research in Medical Science, 2022)
Background: Anal fistulas of crypto-glandular etiology, either simple or complex are common benign surgical conditions. The main treatment is surgery. There is a variety of surgical innovative anal sphincter- saving procedures that are used in the treatment of anal fistulas. Methods: We conducted an extensive review of the literature and tried to cite the most recent publications for anal fistulas. Pub Med and Google Scholar databases were searched for studies related to anal fistulas between 1970 and 2022.Clinical examination and MRI are the main assessment methods of the complexity of anal fistulas and the presence of risk factors related to fail of surgery. Surgical outcomes, complications, and recurrence rates for the most common therapeutic procedures were identified. Results: Simple fistulas are the most common fistulas, treated by fistulectomy or other sphincter sparing techniques with high healing rates of 90%, minor postoperative complications and low recurrence rates. Complex fistulas have more difficult management, optimal surgical outcomes are obtained in 30-80%, and rate of recurrence is higher than in simple fistulas, which results in many patients requiring a second operation. Transphincteric and suprashpincteric fistulas are the most common complex fistulas, more complex fistulas are the supralevator ones or those with long extraspincteric fistulous tracks. The latter are rare in the literature and present difficult surgical management and poor outcomes. Conclusions: Simple fistulas have excellent surgical outcomes. Complex fistulas present more recurrences, but several sphincter-sparing techniques may achieve eventual complete healing, despite recurrences and reoperations. Modern innovative sphincter- saving techniques play an important role in the treatment of simple and complex anal fistulas.